Dreaming the future / making voice / making choice: advocacy for a multiplicative praxis in adult education through an action research project that designs the future - Hunt, Deborah (My University, 2014)
Through Action Research it is the aim of this researcher to explore three broad critically inter-related questions in relation to the field of adult education in South Africa today and my own work with learners in an English Level 4 /4 a Language classroom. The questions are the following: • Given that we are presently living in a world of vastly accelerated change, what are the policies, practices and needs of adult learners that must be taken into consideration and/or promoted if adult education provisioning in the South African context is to be successful in general, and if it is to be enabling for learners, more specifically, in the English 'second’ language classroom? • Secondly, given the historical imbalances of the past, are the needs of blackwomen, as members of the adult learner field, being adequately addressed by policies and practices in adult education provisioning as it is being provided by the State and/or other service providers at present? • If not, what considerations and recontextualisations will promote critically social transformative action that is geared towards gender equity and provision in both official policy documents and local practices? Might these recontextualisation processes critically engage with questions around: changing technologies, Through Action Research it is the aim of this researcher to explore three broad critically inter-related questions in relation to the field of adult education in South Africa today and my own work with learners in an English Level 4 /4 a Language classroom. The questions are the following: • Given that we are presently living in a world of vastly accelerated change, what are the policies, practices and needs of adult learners that must be taken into consideration and/or promoted if adult education provisioning in the South African context is to be successful in general, and if it is to be enabling for learners, more specifically, in the English 'second’ language classroom? • Secondly, given the historical imbalances of the past, are the needs of blackwomen, as members of the adult learner field, being adequately addressed by policies and practices in adult education provisioning as it is being provided by the State and/or other service providers at present? • If not, what considerations and recontextualisations will promote critically social transformative action that is geared towards gender equity and provision in both official policy documents and local practices? Might these recontextualisation processes critically engage with questions around: changing technologies, Through Action Research it is the aim of this researcher to explore three broad critically inter-related questions in relation to the field of adult education in South Africa today and my own work with learners in an English Level 4 /4 a Language classroom. The questions are the following: • Given that we are presently living in a world of vastly accelerated change, what are the policies, practices and needs of adult learners that must be taken into consideration and/or promoted if adult education provisioning in the South African context is to be successful in general, and if it is to be enabling for learners, more specifically, in the English 'second’ language classroom? • Secondly, given the historical imbalances of the past, are the needs of blackwomen, as members of the adult learner field, being adequately addressed by policies and practices in adult education provisioning as it is being provided by the State and/or other service providers at present? • If not, what considerations and recontextualisations will promote critically social transformative action that is geared towards gender equity and provision in both official policy documents and local practices? Might these recontextualisation processes critically engage with questions around: changing technologies, differential power relations (female/male) and unbalanced structural relations in social institutions (race/gender), usefully? What do critical race feminists say and what can we learn from them as we attempt to put into place an enabling legislative framework for the adult education field, possibly before 1999 elections? It is a tenet of this research that the field of adult education cannot be examined in isolation to other fields in the South African context. It is for this reason, that recent policy documents from the department of Adult Education and Training (AET Directorate: 1997a and 1997b) are set against other contractual frames of reference such as the Constitution (Act 108:1996) and the Employment Equity Bill (Department of Labour: 1997), for example, to elicit trends, gaps, ideological contradictions, convergences and positive gains so that the project of transformation might be taken further. Texts by learners are taken in this research as ‘discourse articulations’ through which I consider seriously the above and the meanings made by learners in needs analysis interviews, questionnaires, class discussions, writing sessions and in a classroom newspaper production and design process known as the Simiwye Adult Afewspaper (See Appendix One). Learners’ work as 'cognitive action and hard work’ (Kress: 1997, xxi), provides valuable insights that can, I believe, inform usefully new formulations for future provisioning in adult education that are more complex and closely tuned to adult learners’ own 'lived’ realities and needs, than those being presently circulated in the field by 'experts’. The year of 1998, sees public adult learning centres in a state of crisis. On the programmed day of opening at the beginning of the year, all centres in Gauteng province were temporarily closed down by the State because of 'budget constraints’. This happened in other provinces as well, so that the new learning year of previously attending adult learners at public learning centres was disrupted. Though centres were later reopened in March, the disruption to the learning year has had negative continuing effects for both adult learners and adult education practitioners. As a result, many have left centres entirely, while those who still are present question what may be salvaged of a thwarted year. Originally as a practitioner/researcher, I planned to draw closely on my experiences with learners in the making of the Simunye Adult Afetrepaper (1997), to forward recommendations for curricular practice in the adult education 'second’ language classroom. The value of the communicative processes that went into the making of the newspaper with learners still stands, while 'this moment’ in adult education urges for research support that is less nuclear and more broadly enabling when budgets vii threaten to cut provision entirely and contractual frames of reference fail to provide protection for adult learners and educators, so that they are inhibited from fully enjoying what is their right. The Simunye Adult A’fiivspaper (1997) (See Appendix One) is then always at the centre of this research, though not always fully in view. It is the backdrop to all that has gone before the 'present moment’ and to all that I say now in making a case for the adult education learner. Indeed, my learners make their own case in their own words through the newspaper project, so that this research paper is as 'supporting act’ to what they say. What learners don’t say in the newspaper is that they are being gravely short-changed by the South African system, yet again. I draw then on non-reductive sociological accounts to situate this present moment in wider global context, as it is aligned to an instrumentalist rationality that reifies relations (and humans) in favour of power and money. This is what is happening in the field of adult education at present. Adult learners and their needs are held at bay, so as not to 'distort’ or 'tax’ budget allocations that are increasingly smaller. I show then that two of the most serious flaws in adult education at present are to do with questions of conceptualisation and political will. Changing these means that enabling future projects - like the Simunye Adult Aewspaper that recontextualise the possible to promote real learning change to occur in leamers-in-need-of-access -won’t be aborted stillborn. “All o f us w ith m ultiple consciousness must help society address the needs o f those m ultiply burdened first. R estructuring and rem aking th e world, where necessary, w ill affect those w ho are singularly disadvantaged as w ell. By designing programs that operate on m ultiple levels o f consciousness and address m ultiple levels o f need, w e w ill a ll be able to reach our true potential to the benefit o f ourselves, our fam ilies, our profession, our country, and the world” (Wing:1997a, B2-B)(emphasis unchauged). “We, as black wom en, can no longer afford to th in k of ourselves or let th e law thin k of us as m erely th e sum of separate parts that can be added togeth er or subtracted from, until a w hite m ale or fem ale stands before you. The actuality o f our layered experience is multiplicative. Multiply each of my parts together, 1 x 1 x 1 x 1 x 1, and you have one indivisible being. If you divide one o f these parts from one you still have one” (Ibid., 81)(emphasis unchanged).
Thesis (M.A. (English Education)--University of the Witwatersrand, Faculty of Arts, 1998.